2022
DOI: 10.3390/antibiotics11080991
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use and Bacterial Infection in COVID-19 Patients in the Second Phase of the SARS-CoV-2 Pandemic: A Scoping Review

Abstract: This scoping review aimed to explore the prevalence and patterns of global antibiotic use and bacterial infection in COVID-19 patients from studies published between June 2020 and March 2021. This review was reported in line with the Preferred Reporting of Systematic Reviews and Meta-Analyses (PRISMA) extension for Scoping Reviews, and the protocol is registered with the Open Science Framework. Compared with our previously-published review of the period (December 2019–June 2020), the antibiotic prescribing rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
3
15
1
4
Order By: Relevance
“…This review points to a large dissociation between evidence of bacterial infection and the use of antimicrobials, as only 16% of studies reported indications of bacterial infection, while 54% of patients received empirical antibiotic therapy. ( 37 ) Furthermore, it should be mentioned that critically ill COVID-19 patients admitted to the ICU may have higher rates of secondary bacterial infection, reaching more than 50% of cases. ( 38 )…”
Section: Discussionmentioning
confidence: 99%
“…This review points to a large dissociation between evidence of bacterial infection and the use of antimicrobials, as only 16% of studies reported indications of bacterial infection, while 54% of patients received empirical antibiotic therapy. ( 37 ) Furthermore, it should be mentioned that critically ill COVID-19 patients admitted to the ICU may have higher rates of secondary bacterial infection, reaching more than 50% of cases. ( 38 )…”
Section: Discussionmentioning
confidence: 99%
“…Результаты, полученные C. Murray и соавт., указывают на то, что 4,95 млн смертей во всем мире за 2019 г. связаны наличием АБР бактерий к назначаемым АБ [5]. Специалисты Всемирной организации здравоохранения и многочисленные исследователи также подчеркивают, что распространение АБР к противомикробным препаратам является актуальной проблемой, требующей глобального, скоординированного алгоритма действий, направленных на решение складывающейся ситуации [1,[6][7][8][9].…”
Section: введение антибиотикорезистентностьunclassified
“…По данным W. Cong и соавт. установлено, что общий показатель назначения АБ пациентам с COVID-19 снизился с 82,3 до 39,7% в период с декабря 2019 по июнь 2020 г. и с июня 2020 по март 2021 г. соответственно [6].…”
Section: введение антибиотикорезистентностьunclassified
“…This is done in the hope of eliminating any potential bacterial infections that may be present, as the mortality rates are higher in patients who have a co-infection or a superinfection [ 27 , 28 , 29 ]. In spite of the fact that antibiotic use may be helpful, it is important to point out that there is a potential danger of developing antimicrobial resistance when using antibiotics; as a result, the choice of whether or not to receive antibiotic therapy ought to be considered carefully [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%